2020
DOI: 10.12928/telkomnika.v18i6.16970
|View full text |Cite
|
Sign up to set email alerts
|

A beamforming comparative study of least mean square, genetic algorithm and grey wolf optimization algorithms for multipath smart antenna system

Abstract: Multipath environment is a limitation fact in optimized usage of wireless networks. Using smart antenna and beamforming algorithms contributed to that subscribers get a higher-gain signal and better directivity as well as reduce the consumed power for users and the mobile base stations by adjusting the appropriate weights for each element in the antenna array that leads to reducing interference and directing the main beam to wanted user. In this paper, the performance of three of beamforming algorithms in mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The GA was not utilized as a beamformer in the current study because it is relatively slow in reaching the steady state solution and it requires a large number of iterations. Also, some studies reported that the LMS technique achieves better directivity than GA in multipath environment, which provides sharper and more precise beam patterns [51]. Also, it was reported that GA is not efficient in mitigating interfering sources as LMS [51,52].…”
Section: B Ga-lms Beamforming Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GA was not utilized as a beamformer in the current study because it is relatively slow in reaching the steady state solution and it requires a large number of iterations. Also, some studies reported that the LMS technique achieves better directivity than GA in multipath environment, which provides sharper and more precise beam patterns [51]. Also, it was reported that GA is not efficient in mitigating interfering sources as LMS [51,52].…”
Section: B Ga-lms Beamforming Resultsmentioning
confidence: 99%
“…Also, some studies reported that the LMS technique achieves better directivity than GA in multipath environment, which provides sharper and more precise beam patterns [51]. Also, it was reported that GA is not efficient in mitigating interfering sources as LMS [51,52]. On the other hand, the GA algorithm was proven to be an efficient for array thinning [27,30,31,36] so that it was utilized for thinning the proposed array design.…”
Section: B Ga-lms Beamforming Resultsmentioning
confidence: 99%
“…The search agent's location [X, Y] is modified in accordance with the position of the prey as determined so far [𝑋𝑋 * , π‘Œπ‘Œ * ]. The coefficient vectors 𝐴𝐴 and 𝐢𝐢 are changed to get the optimal agent at various locations [31]. Grey wolves are led by alpha, with help from beta and delta.…”
Section: 𝑋𝑋(𝐾𝐾 + 1) = 𝑋𝑋 𝑝𝑝 (𝐾𝐾) βˆ’ 𝐴𝐴 β€’ 𝐷𝐷mentioning
confidence: 99%
“…Clearly, this antenna needs switching elements that can link/dislink the stubs as intended. PIN diodes are widely used as switching elements in reconfigurable antennas [17], [18]. In this design, six HPND-4005 PIN diodes [19] are inserted to select its mode of operation.…”
Section: Configurationmentioning
confidence: 99%